2017
DOI: 10.1186/s12890-017-0386-6
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of correct technique in patients using pressurized metered dose inhalers

Abstract: BackgroundCorret inhaler technique is recommended by guidelines for optimum asthma care. The objective of the study is to determine real life predictors of correct pressurized metered dose inhaler (pMDI) technique in Asthma and COPD patients.MethodsTwo hundred eight adult patients aged 18+ from respiratory outpatients (69.2%) and the community on regular pMDI for a diagnosis of Asthma (78.9%) or COPD, were recruited. A questionnaire containing 31 possible predictors was administered and pMDI technique with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 25 publications
3
31
1
Order By: Relevance
“…In this study, nearly half of the patients do not perform the essential steps for MDIs correctly (shake the inhaler and remove the protective cap, inhale slowly and simultaneously active the canister), and this result is in agree with what others found . One of the most common problems was failure to hold breath for 5–10 s. This finding on an essential step was also seen in previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, nearly half of the patients do not perform the essential steps for MDIs correctly (shake the inhaler and remove the protective cap, inhale slowly and simultaneously active the canister), and this result is in agree with what others found . One of the most common problems was failure to hold breath for 5–10 s. This finding on an essential step was also seen in previous studies .…”
Section: Discussionsupporting
confidence: 91%
“…One study found that the male gender was a predictor for several correct steps in inhalation technique but not critical ones. 32 This could be explained by the fact that, in general, men have a better hand-to-eye coordination 33 and spatial abilities than women. 34…”
Section: Gendermentioning
confidence: 99%
“…Multiple studies report that more patients make errors with dry powder inhalers [10,15], while others suggest that patients make more errors with metered dose inhalers [2,13,16]. The impact of age on proper inhaler technique is another point of contention, however, a recent systematic review favors a negative correlation between older age and proper inhaler technique [5,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Health care practitioners are failing their patients who suffer from pulmonary conditions. Conversely, studies have also shown that health care practitioners can improve the inhaler technique of their patients and reduce errors [9,18,24,25]. Community pharmacists are particularly situated to regularly check inhaler technique when patients drop off new inhaler prescriptions or pick up refills.…”
Section: Introductionmentioning
confidence: 99%